Les tendances de la stratégie conventionnelle de l’OTAN - Klepak, Harold; George, William (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
The purpose of this article is to concentrate on the conventional strategy of Europe in order to bring to light its new trends, all the while demonstrating the principal role that new technology maintains within this evolutionary process. Emphasis will be placed upon the recent changes in Western doctrines, in order to distinguish the differences between the doctrines of Air Land Battle and Follow-on-Forces Attack (FOFA), and those which preceded them. An attempt will then be made to compare the recent developments in the conceptual models of War of Attrition and War of Maneuver, so as to determine whether these new doctrines correspond to either the first or second model. This analysis should thus permit a better understanding of the debate which encompasses the conventional strategy of Europe.